Strain controlled medium cycle fatigue of a notched Pb-Sn-Cd lead alloy. (October 2019) - Viespoli, Luigi M.; Johanson, Audun; Alvaro, Antonio; Nyhus, Bård; Berto, Filippo
Abstract: During the extrusion process of subsea power cable sheathing layer it is possible that metallic and/or non-metallic debris present in the processing environment enter the metal lattice originating discontinuities that might have a detrimental effect on the fatigue life and the overall integrity of the sheathing. In order to understand the influence of these production defects on the reliability of installed power-lines, a series of specimens directly retrieved from the extruded sheathing were fatigue tested at different strain rates and range both in presence and absence of a non-passing through notch simulating the geometrical discontinuity induced by a particle. In order to collect the necessary information for the understanding of the failure mechanism, Digital Image Correlation and Scanning Electron Microscopy were used to understand the influence of the testing condition on the material resistance and failure mode. Highlights: Notched and un-notched Pb-Sn-Cd lead specimens fatigue tested at different strain rates. The real strain field was obtained by digital image correlation. Fracture surfaces investigated by SEM. The notch sensitivity if found to be decreasing with increasing strain range.